IMPLEMENTATION OF THE EXPERIENCE OF ATO AND OYF BY THE ARMED FORCES OF UKRAINE FOR DETERMINING THE REQUIREMENTS TO PROFESSIONAL TRAINING OF MILITARY SPECIALISTS - Skriabin, O.; Chernykh, Yu.; Chernykh, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article is based on the analysis of the main factors taking place at this time, substantiates the relevance of determining (clarifying) the requirements for professional training of military specialists trained in higher military educational institutions in the field of knowledge "Military Sciences, National Security, State Border Security". The study is based on the fact that at present the general list of requirements for military specialists is defined in the relevant professional standards, standards of higher education and educational programs for their training in each specialty at certain levels of education. These requirements are formulated in terms of competencies and learning outcomes. The purpose of the study is to try to justify the feasibility of implementing the experience of the anti-terrorist operation (ATO) and the Joint Forces (JFO) operation of the Armed Forces of Ukraine in determining the requirements for professional training of officers. It is established that the level of training and the general list of competencies that a graduate of a military educational institution has does not fully meet the needs of the modern army. This is clearly evidenced by the experience of hostilities in eastern Ukraine. Analysis of hostilities has shown that the list of tasks to be solved by the military is constantly expanding. Today, in addition to combat missions, they are increasingly involved in solving problems of a socio-humanitarian nature, which requires the formation of both professional and social components of the potential of the soldier's personality. Along with the increase in the requirements for the general level of professional training of military specialists, new requirements for their social and humanitarian training appear. The following new requirements for training are considered: raising the level of leadership qualities of an officer; formation of his personal values and clear personal goals; the ability to counteract the information and psychological influences of the enemy within the information confrontation; ability to establish communications between military units and the local population in the area of hostilities, etc. The analysis is carried out and the essence of the specified requirements is revealed. To solve the research tasks, a system of general scientific and special methods of theoretical and empirical research was used, namely theoretical and methodological analysis of the problem, systematization and generalization of information concerning the essence and content of certain tasks, monitoring of the existing system of military training. system approach, expert evaluation, analysis and interpretation of the obtained empirical data.
Keywords: military specialists, professional training, higher military educational institutions; competencies; requirements; experience of antiterrorist operation and environmental protection